2016
DOI: 10.1002/admt.201600230
|View full text |Cite
|
Sign up to set email alerts
|

Slot Die Coated and Flexo Printed Highly Efficient SMOLEDs

Abstract: A basic solution‐processable organic light‐emitting diode (OLED) stack comprising two organic layers is presented in this study. The hole injection layer (poly(3,4‐ethylenedioxythiophene)‐poly(styrenesulfonate), PEDOT:PSS) is slot die coated and flexographically printed for process comparison in terms of film homogeneity and the device performance. The emissive layer consisting of a small molecule host–guest system with a green triplet emitter is slot die coated. The single layer thicknesses are mapped by an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 75 publications
0
27
0
Order By: Relevance
“…On the one hand, oxygen or argon plasma as a pretreatment step to increase the surface energy of the substrate is widely spread and is commonly used in literature [9][10][11]. On the other hand, wettability can be improved by reducing the surface tension of the ink by adding surfactants, such as Triton-X for water-based formulations [12,13]. The material class of small molecules is particularly interesting due to the higher efficiency compared to polymers but also more challenging regarding solution processing [14].…”
Section: State Of the Art Of Printed Multilayer Oledsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, oxygen or argon plasma as a pretreatment step to increase the surface energy of the substrate is widely spread and is commonly used in literature [9][10][11]. On the other hand, wettability can be improved by reducing the surface tension of the ink by adding surfactants, such as Triton-X for water-based formulations [12,13]. The material class of small molecules is particularly interesting due to the higher efficiency compared to polymers but also more challenging regarding solution processing [14].…”
Section: State Of the Art Of Printed Multilayer Oledsmentioning
confidence: 99%
“…If the coating is not applied continuously but in a S2S mode, it has to be considered that it takes a few seconds until the coating solution has bridged the gap between slot die and substrate and until a state of equilibrium between the delivered and applied volume is reached [12]. In order to achieve a steady-state mode as quickly as possible, the substrate movement can be started delayed to the pumping process; additionally, the inlet zone can be extended (if possible) or glass instead of plastic syringes may be used [13,31]. Otherwise, a layer thickness gradient in the coating direction can occur; for example a thickness increase from 66 nm to 88 nm was observed for a slot-die-coated green emissive material over a coating length of 131 mm [13].…”
Section: Slot Die Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Research aimed at results more directly applicable in an industrially relevant production environment therefore focuses on other techniques, like slotdie coating. 8,[11][12][13][14] This approach exhibits its own specific challenges not encountered in vacuum processing, but there are also distinct benefits associated with it, which, for certain application areas, show good prospects for replacing dry deposition technologies on the mid-term. Many of these beneficial characteristics are related to the possibility of processing at atmospheric pressure, with more efficient materials use, high throughput, and at low overall production cost.…”
Section: Introductionmentioning
confidence: 99%
“…15 Several recent publications have demonstrated that slot-die coating can be used for the production of highly efficient OLED devices by solution based techniques. [11][12][13][14] These studies, however, have all made use of sheet-to-sheet (S2S) processing. An especially interesting aspect of slot die coating and several other solution processing methods is production upscaling by roll-to-roll (R2R) manufacturing techniques.…”
Section: Introductionmentioning
confidence: 99%